Articulated structure of the Igbo tense phrase domain (2021)
"The tense phrase (TP) domain is the domain that expresses grammatical tense, aspect and mood. Existing studies concentrated on describing the morph-syntactic features of the Igbo TP categories with little attention paid to their interaction and hierarchical order. This study, therefore, investigates the morpho-syntactic features and interaction of the functors with a view to determining their hierarchical order in the clause structure. Primary and secondary data were collected and subjected to syntactic analysis. Three main functors, Tense, Aspect and Negation, overtly occur in the Igbo TP area as verbal affixes and they exhibit two opposing patterns of morpheme order: V-T-ASP-NEG and T-ASP-NEG-V. The former, where the functors follow the verb, requires obligatory movement of the VP to spec TP, while the latter requires no such movement since the functors precede the verb. The study demonstrated that these morpheme orders are derived syntactically via operation merge with surface order corresponding to the hierarchical order. This is in contrast to preceding studies which assume mirror image where the linear order is the inverse of the hierarchical order.